"My School and Me"—Exploring the Intersections of Insideness and Interior Environments. Issue 4 (December 2013) - Strickland, Aileen; Hadjiyanni, Tasoulla
ABSTRACT Much of the scholarship on place and identity draws from fields like psychology, anthropology, and geography and as a result, interior environments have not been the focus. Understanding how interiors intersect with the self‐making process is crucial to the field of interior design, on both theoretical and practical levels. This is particularly the case for learning environments, the places where children spend much of their day at crucial junctures of their development and establishment of self. Through the experiences of six high‐school students from an inner city Minneapolis high‐school, this paper explores how the concept of "insideness, " first conceptualized by E. Relph (1976), can be appropriated to understand the person–interiors relationship. Photographs, journals, and personal interviews shed light on the process by which "insideness" is constructed in interiors. With walls being noted as the primary constructor of "insideness, " the analysis unravels the active seeing of the students across spatial scales and how characteristics of spaces inform how students contest and negotiate their identity. Through constructing and deconstructing their understandings of both the interiors they inhabit and themselves, students navigate larger societal and cultural messages. We call this exploratory theoretical model The Spatial Scales of Self‐Making. By attempting to appropriate the term "insideness" and theorize the relationship between identity and interiors as one dependent on varying spatial scales within the interior environment, this paper begins to move discourses away from a monolithic understanding of interiors. Scholars, educators, and practitioners of interior design who recognize that design parameters that range from programming to spatial layout, material selection, and signage can play a role in these meaning‐making processes can help push the boundaries of what it means to create spaces and places in which people who are seers live their lives.